Inovasi Mall Pelayanan Publik untuk Peningkatan Kualitas Pelayanan Publik di Kabupaten Kulon Progo - Riski Puspita Lestari; Dyah Mutiarin; Achmad Nurmandi (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2020)
Improving the quality of public services is done through bureaucratic reform through the Ministry of State Empowerment and Bureaucratic Reform (KEMENPANRB) making one of the latest innovations in making excellent service. Public Service Malls are basically the integration of public services from the regions with various public services of the central government, BUMN and private. This research uses descriptive qualitative research method with analysis through Nvivo12 Plus application with crosstab feature and matrix query rate (%). The results of this study are: first, the relative benefits obtained from MPP in Kulon Progo Regency. This society is the most dominant in getting its benefits. Second, the compatibility or adjustment of MPP in Kulon Progo is more in line with the needs and has been planned by DPMPT. Third, the complexity or complexity of MPP innovation in Kulon Progo can be easily accessed by service users. Fourth, triability shows that MPP has really been tested, then each of them starts innovation, in this study the community also conducts a trial that is by accessing the services that are in MPP. Fifth, the observability of producing MPP can be seen by the recipient of this innovation in this case the community, so this is also the most dominant factor of society compared to the others.